2022
DOI: 10.3389/fnut.2022.1019259
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-rich extract from black beans exerts anti-diabetic effects in rats through a multi-genomic mode of action in adipose tissue

Abstract: Black beans (BB) are an important source of a range of plant bioactive compounds including polyphenols, particularly anthocyanins. Several studies support that consumption of BB is associated with health benefits, including prevention of type 2 diabetes mellitus (T2DM). However, molecular mechanisms underlying the potential health properties of BB on adipose tissue (AT) are still largely unknown. The purpose of this study was to investigate multi-genomic effects of BB intake and identify regulatory networks po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Black soybean seed coats containing anthocyanins have been used in traditional oriental medicine for various health benefits. Thus, nutraceuticals in the form of black bean extracts or supplements may be developed to treat hypertension, diabetes, and cardiovascular diseases, potentially by reducing oxidative stress and inflammation [155,156].…”
Section: Legumes and Their By-products As Ingredients In Functional F...mentioning
confidence: 99%
“…Black soybean seed coats containing anthocyanins have been used in traditional oriental medicine for various health benefits. Thus, nutraceuticals in the form of black bean extracts or supplements may be developed to treat hypertension, diabetes, and cardiovascular diseases, potentially by reducing oxidative stress and inflammation [155,156].…”
Section: Legumes and Their By-products As Ingredients In Functional F...mentioning
confidence: 99%
“…Several studies support that consuming these phytochemicals is associated with health benefits. Particularly, anthocyanin consumption has been associated with the prevention of type 2 diabetes mellitus ( 82 ), the prevention of metabolic diseases and obesity ( 32 , 83 ), the cardio-protective potential, the protection of the gastrointestinal tract from high fat diet-induced alterations in redox signaling, barrier integrity and dysbiosis ( 84 ), the anticancer effects ( 85 ), and the decreased oxidative stress and inflammation ( 86 ), and many other positive effects on human health ( 3 ).…”
Section: The Molecular Structure and Role Of Polyphenolic Compounds F...mentioning
confidence: 99%
“…These molecules play an important role in the prevention of obesity and diabetes. It is suggested that once absorbed, they may positively modulate GLUT4 in adipose tissue and skeletal muscle and/or affect the gut microbiota and thus impact consumer health [52][53][54]. Evidence shows that their consumption generates other beneficial health effects [52,53].…”
Section: Black Beansmentioning
confidence: 99%
“…It is suggested that once absorbed, they may positively modulate GLUT4 in adipose tissue and skeletal muscle and/or affect the gut microbiota and thus impact consumer health [52][53][54]. Evidence shows that their consumption generates other beneficial health effects [52,53]. Hernandez-Velazquez and colleagues evaluated the effects of the consumption of whole cooked bean flour and a bean protein concentrate on body composition, energy expenditure, and glucose metabolism in an animal model fed with a high-fat/high sucrose diet.…”
Section: Black Beansmentioning
confidence: 99%